The Vulnerability Assessment of Flash Floods Disaster in the Upper Cisadane Watershed - Wardhani, Fitriany Amalia; Pravitasari, Andrea Emma; Ridwansyah, Iwan (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
Flash floods is a sudden flood disaster that can be triggered by several factors, one of which is the landslides that occur in river basins. In Bogor Regency, there are fourteen sub-districts located in the Upper Cisadane watershed area that are prone to flash flood disaster. This study aims to determine social, economic, physical and environmental vulnerability assessment of the community in the Upper Cisadane watershed area based on the modification assessment from PERKA BNPB No. 12 Tahun 2012. According to the vulnerability index, the Upper Cisadane watershed has high and very high classes of flash floods vulnerability. Sub-districts with high vulnerability index class are Nanggung, Pamijahan, West Bogor, South Bogor, Central Bogor, East Bogor, Cibungbulang, Cigudeg, Leuwisadeng, and Sukajaya, meanwhile, sub-districts with very high vulnerability index are Caringin, Ciampea, Ciawi, Cigombong, Cijeruk, Ciomas, Dramaga, Kemang, Leuwiliang, Megamendung, Rancabungur, Rumpin, Tamansari, and Tenjolaya.